Kaitan antara Kemandirian Belajar dengan Prokrastinasi Akademik - Vincencius William Lorenzo; Prias Hayu Purbaning (Solution : Journal of Counselling and Personal Development, 2022)
This research aimed to 1) Describe students’ autonomous learning level in SMPN 1 Minggir, 2) Describe students’ academic procrastination level in SMPN 1 Minggir, 3) Find out the relationship between autonomouslearning and academic procrastination in 9th-grade students in SMPN 1 Minggir. This study used descriptive quantitative research with a correlational research design. The sample used in this study was the 9thgrade students in SMPN 1 Minggir with a total of 93 respondents. The data gathering technique used in this research was a survey that was conducted online by distributing the Google form. The total valid items on the scale of autonomous learning were 93 items, meanwhile, the total valid items on the scale of academic procrastination were 38 items. The testing of the reliability coefficient instrument in this research used the Alfa Cronbach technique. The result of the reliability testing instrument on the autonomous learning level was 0.879 and the academic procrastination level was 0.770. Both instruments were tested as reliable and worth using. The result of this study found that 1) The yield achievement of the autonomous learning level indicated the tendency at a high level, 2) The yield achievement in academic procrastination level indicated the tendency at a medium level, 3) The result analysis of the correlational hypothesis indicated r value in the amount of 0.487 with the significance value 0.0000.05. The result showed a significant positive relationship between autonomous learning and academic procrastination in 9th-grade students in SMPN 1 Minggir.